2010
DOI: 10.1007/s12011-010-8714-1
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Supplementation Reduces the Blood Cholesterol Levels in Ca-Deficient Ovariectomized Rats

Abstract: Manganese (Mn) is an essential element for normal development and bodily functions in humans. In the present study, we examined whether Mn supplementation can alter the serum lipid parameters and liver function in Ca-deficient ovariectomized (OVX) rats. Sixty female Sprague-Dawley rats (6 weeks) were divided into five groups and bred for 12 weeks: sham-operated control group (Sham), OVX Ca deficiency group (OLCa) with Ca-deficient diet (0.1% Ca modified AIN-93N diet), OVX Ca deficiency and Mn supplementation g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
3
19
0
1
Order By: Relevance
“…The oral administration of OHS significantly (p<0.05) suppressed serum GOT and GPT elevation when compared to the OVX group. The serum GPT and GOT levels often increase in response to liver injury, fatty liver and hepatitis (49). In the present study, decreases in the levels of GPT and GOT were observed in the OHS groups, suggesting that OHS confers protection on liver tissues against damage or disease.…”
Section: Effects Of Ohs On Hepatic Enzymes In Serumsupporting
confidence: 58%
“…The oral administration of OHS significantly (p<0.05) suppressed serum GOT and GPT elevation when compared to the OVX group. The serum GPT and GOT levels often increase in response to liver injury, fatty liver and hepatitis (49). In the present study, decreases in the levels of GPT and GOT were observed in the OHS groups, suggesting that OHS confers protection on liver tissues against damage or disease.…”
Section: Effects Of Ohs On Hepatic Enzymes In Serumsupporting
confidence: 58%
“…Group B was supplemented with a 16 mg/kg of body weight dose of Mn 2ϩ . Previous studies have used 0.001% Mn 2ϩ in the diet as an adequate amount and 0.01% Mn 2ϩ as supplementation (19,20). Various studies have reported daily food consumption for ZDF rats to range between 35 and 50 g per day (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…Manganese helps the body form connective tissue, bones, blood clotting factors, and sex hormones (Santamaria and Sulsky, 2010). It also plays a role in lipid and carbohydrate metabolism, calcium absorption, and blood glucose regulation (Kehl-Fie and Skaar, 2010;Bae et al, 2011). Manganese is also necessary for normal brain and nerve function.…”
Section: Nutritional Value Of Beefmentioning
confidence: 99%